Human-facility interaction improving people’s understanding of service robots and elevators - system design and evaluation - Adachi, Mau; Kakio, Masayuki (Frontiers in Robotics and AI, 2025)
As service robots become increasingly integrated into public spaces, effective communication between robots and humans is essential. Elevators, being common shared spaces, present unique challenges and opportunities for such interactions. In this study, we developed a Human-Facility Interaction (HFI) system to facilitate communication between service robots and passengers in elevator environments. The system provided both verbal (voice announcements) and non-verbal (light signals) information to passengers waiting for an elevator alongside a service robot. We installed the system in a hotel and conducted two experiments involving 31 participants to evaluate its impact on passengers’ impressions of the elevator and the robot. Our findings revealed that voice-based information significantly improved passengers’ impressions and reduced perceived waiting time. However, light-based information had minimal impact on impressions and unexpectedly increased perceived waiting time. These results offer valuable insights for designing future HFI systems to support the integration of service robots in buildings.